The Effects of the Learning Design by using STAMP Model for Comprehensive Geriatric Assessment Training in Nursing Students, Boromarajonani College of Nursing, Udon Thani - Chaiwongsa, jaruporn; Sukontawat, Watjana (Journal of The Royal Thai Army Nurses, 2026)
This quasi-experimental study aims to (1) compare mean differences in knowledge scores of the experimental group before and after intervention, (2) compare mean differences in knowledge scores between experimental and control groups, and (3) examine the learners’ satisfaction with STAMP model education. A total of 28 participants were included from a purposively selected group. The data were collected using the STAMP model for Comprehensive Geriatric Assessment training, gerontology nursing examinations, and a questionnaire on the effects of STAMP model education. Data were analyzed using descriptive statistics, including percentage, mean, and standard deviation, and inferential statistics using Paired-sample t-test and Independent sample t-test. The results showed that mean differences in knowledge scores of the experimental group significantly increased (p < .05). Comparing the mean differences in knowledge scores between groups, they were significantly different (p < .05). The overall mean satisfaction score of nursing students toward the STAMP model education was 4.11, indicating a high level of satisfaction. Therefore, the STAMP model should be applied to academic courses that aim to enhance analytical thinking skills, as it provides a useful approach for advancing nursing education.